Implementasi Model Pembelajaran Berbasis Puzzle Kisah Nabi dalam Perencanaan Pembelajaran Pendidikan Agama Islam - Sani Latifatul Khilmina (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study aims to describe the implementation of the Prophets’ Story Puzzle learning model in Islamic Religious Education (PAI) lesson planning and to analyze its effectiveness in enhancing students’ motivation and understanding of Islamic values. The research employed a descriptive quantitative approach, involving Islamic Education teachers and ninth-grade students at a Madrasah Tsanawiyah (Islamic junior high school). Data were collected through classroom observation, in-depth interviews, and analysis of students’ worksheets. Data analysis followed Miles and Huberman’s interactive model, consisting of data reduction, data display, and conclusion drawing and verification. The findings revealed that the implementation of the Prophets’ Story Puzzle significantly improved students’ engagement and motivation, increasing participation from 60% to 83% and the average understanding of Islamic values from 68 to 84. Students demonstrated strong emotional involvement and were able to relate the stories of the Prophets, such as Abraham, Joseph, and Noah, to real-life experiences. This model also supports Contextual Teaching and Learning (CTL) by fostering collaboration, critical thinking, and deeper spiritual reflection. Therefore, the Prophets’ Story Puzzle model is proven relevant as an innovative approach to modern Islamic Religious Education, integrating cognitive, affective, and psychomotor aspects harmoniously, and transforming PAI learning into an enjoyable, contextual, and meaningful experience. Keywords: Islamic Religious Education, Prophets’ Story Puzzle, Learning Innovation, CTL, Islamic Values